Tritium and deuterium labelling of a kainate receptor antagonist and evaluation as a radioligand - Chałupnik, Paulina; Marek, Aleš; Hovah, Marie Emilie Leiticia; Pickering, Darryl S; Temperini, Piero; Donbosco, Stephanie; Szymańska, Ewa; Johansen, Tommy N (Journal of labelled compounds & radiopharmaceuticals, 2024)
Kainate receptors play a crucial role in mediating synaptic transmission within the central nervous system. However, the lack of selective pharmacological tool compounds for the GluK3 subunit represents a significant challenge in studying these receptors. Recently presented compound 1 stands out as a potent antagonist of GluK3 receptors, exhibiting nanomolar affinity at GluK3 receptors and strongly inhibiting glutamate-induced currents at homomeric GluK1 and GluK3 receptors in HEK293 cells with Kb values of 65 and 39 nM, respectively. This study presents the synthesis of two potent GluK3-preferring iodine derivatives of compound 1, serving as precursors for radiolabelling. Furthermore, we demonstrate the optimisation of dehalogenation conditions using hydrogen and deuterium, resulting in [2H]-1, and demonstrate the efficient synthesis of the radioligand [3H]-1 with a specific activity of 1.48 TBq/mmol (40.1 Ci/mmol). Radioligand binding studies conducted with [3H]-1 as a radiotracer at GluK1, GluK2, and GluK3 receptors expressed in Sf9 and rat P2 membranes demonstrated its potential applicability for selectively studying native GluK3 receptors in the presence of GluK1 and 2-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor-blocking ligands.
Keywords: Deuterium; Humans; tritium; AMPA receptory; Glutamic Acid; krysa rodu Rattus; lidé; HEK293 Cells; zvířata; deuterium; receptory kyseliny kainové; tritium labelling; quinoxaline‐2,3‐diones; Tritium; HEK293 buňky; Rats; Animals; Receptors, Kainic Acid; ionotropic glutamate receptors; Receptors, AMPA; kyselina glutamová